2007
DOI: 10.1529/biophysj.106.101881
|View full text |Cite
|
Sign up to set email alerts
|

Specific Adsorption of Osteopontin and Synthetic Polypeptides to Calcium Oxalate Monohydrate Crystals

Abstract: Protein-crystal interactions are known to be important in biomineralization. To study the physicochemical basis of such interactions, we have developed a technique that combines confocal microscopy of crystals with fluorescence imaging of proteins. In this study, osteopontin (OPN), a protein abundant in urine, was labeled with the fluorescent dye AlexaFluor-488 and added to crystals of calcium oxalate monohydrate (COM), the major constituent of kidney stones. In five to seven optical sections along the z axis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
128
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(143 citation statements)
references
References 43 publications
14
128
1
Order By: Relevance
“…Fluorescent molecules and fluorescently-tagged proteins have been previously and effectively used to study protein-mineral interactions (in COM studies (19,20,(77)(78)(79)). Extending this approach to COD and using a poly-Asp 86 -93 peptide not previously examined by others, we have visualized by light and confocal microscopy the incorporation behavior of this peptide into the crystal structure of COD and revealed distinctive and informative three-dimensional sectoral (compositional) zoning patterns (77)(78)(79)(80) that provide significant new insight into protein occlusion into biominerals.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescent molecules and fluorescently-tagged proteins have been previously and effectively used to study protein-mineral interactions (in COM studies (19,20,(77)(78)(79)). Extending this approach to COD and using a poly-Asp 86 -93 peptide not previously examined by others, we have visualized by light and confocal microscopy the incorporation behavior of this peptide into the crystal structure of COD and revealed distinctive and informative three-dimensional sectoral (compositional) zoning patterns (77)(78)(79)(80) that provide significant new insight into protein occlusion into biominerals.…”
Section: Discussionmentioning
confidence: 99%
“…Because biominerals often show complicated architecture that cannot be achieved by chemical synthetic pathways in artificial systems, the process is attractive in the fields of materials development and science (Cha et al, 1999;Aizenberg et al, 2003;Garcia-Ruiz et al, 2009). Molecular studies on biomineralization have shown that the process involves a number of proteins that function as molecular templates (Du et al, 2005;Sugawara et al, 2006), a nucleation factor (Lakshminarayanan et al, 2002), a growth inhibitor (Marin et al, 2007;Taller et al, 2007), framework (Meldrum et al, 1991), and a catalyst (Cha et al, 1999). Recent transmission electron microscopic analyses of biominerals indicated that the micrometer-sized biomineral crystals consist of small grainy crystals, ranging in size from approximately 10 to 200 nm, depending on the biomineral types (Oaki et al, 2006;Nemoto et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The size and shape of the small crystals are uniform and well-regulated in individual biological systems, suggesting that these are the minimal unit of biomineral crystals, which assemble to form micrometer-scaled biomineral crystals (Cölfen and Antonietti, 2005;Oaki et al, 2006). Although many proteins have been isolated from a variety of biominerals, their functions have mainly been described in the synthesis of micrometer-sized biomineral crystals (Cha et al, 1999;Lakshminarayanan et al, 2002;Du et al, 2005;Sugawara et al, 2006;Marin et al, 2007;Taller et al, 2007). The control mechanisms of morphology and size of the minimum unit of biomineral crystals remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Ansocalcin, a protein isolated from goose eggshell matrix, induces the construction of spherical calcite polycrystalline aggregates (6). Osteopontin, a protein that is abundant in urine, interacts with the specific crystal edges of calcium oxalate and influences the morphology of the crystals (7). In recent years, it has been determined that hierarchical organized structures with highly uniform pseudo-hexagonal structures are involved in the formation of the sturdy nacreous layer of mollusk shells and that rhombohedral nano-sized crystals are involved in the development of egg shells (3, 8 -9).…”
mentioning
confidence: 99%